Teaching and learning in diverse classrooms: Faculty reflections on their experiences and pedagogical practices of teaching diverse populations - Castaneda, Carmelita Patrice (Rosie) (ScholarWorks@UMass Amherst, 2002)
The composition of classrooms in higher education is rapidly becoming more diverse, presenting new challenges to faculty regarding their teaching and curricular practices. One response in higher education has been the emergence of development programs aimed at helping faculty provide successful, quality education to diverse students. This study describes how faculty who participated in the Teaching and Learning in the Diverse Classroom (TLDC) Faculty and TA Partnership Project (1994–2000) at the University of Massachusetts, Amherst, reflected on their experiences and pedagogical practices as instructors in diverse classrooms. Participants were faculty members who exhibited variety across academic disciplines, levels of faculty rank, gender, race, and ethnicity. The procedure for this investigation employed quantitative and qualitative research methods. There were 29 responses to the mailed surveys and 10 interviews with participants, some of whom also responded to the mailed survey. The surveys were analyzed for possible correlations between gender and race in participants' responses; the interviews were analyzed for the possible relationships of gender in participants' responses. Whereas participants provided many different accounts of what diversity meant to them as instructors, they unanimously agreed that considerations of diversity were important to their teaching in diverse classrooms. This study's surveys and interviews generated strategies for improving faculty teaching and curricular practices—including the use of student-focused methods, multiple methods, course readings, and considerations of the teaching self—identified by faculty as components central to their perceptions of their experiences and teaching practices with diverse students. Additional strategies, such as fostering community in the diverse classroom and student-focused assessment, emerged from the interview data. Survey responses focused on a personal approach to faculty's sense of their growth as educators in diverse classrooms, whereas interview findings highlighted the need for further institutional support. This research may help development programs, such as the TLDC Project, provide continuing support for faculty to offer successful, quality education to multicultural classrooms.